IMAGE OF THE WORLD AND COGNITIVE MAP AS METHODS OF COGITATIVE ACTIVITY DESCRIPTION - Denis F. Dautov (Advanced Engineering Research)
The theoretical research on the “image of the world” and “cognitive map” concepts is resulted. Their basic constituents are identified and described. The qualitative analysis of the obtained data is given.